High resolution flat-panel CT arthrography vs. MR arthrography of artificially created osteochondral defects in ex vivo upper ankle joints. - Gesa H Pöhler (Public Library of Science (PLoS), 2021)
Purpose High resolution flat-panel computed tomography arthrography (FPCT-A) and magnetic resonance arthrography (MR-A) are well suited to evaluate osteochondral lesions. The current study compares the performance of FPCT-A versus MR-A in an experimental setting. Methods Fourteen cadaveric ankles were prepared with artificial osteochondral defects of various sizes in four separate talar locations. After intra-articular contrast injection, FPCT-A and 3-T MR-A were acquired. Each defect was then filled with synthetic pallets. The resulting cast was used as reference. Two independent radiologists measured the dimensions of all defects with FPCT-A and MR-A. Intra-class correlation coefficients (ICC) were calculated. Data were compared using t-tests and Bland-Altman plots. Results The correlation for FPCT-A and cast was higher compared to MR-A and cast (ICC 0.876 vs. 0.799 for surface [length x width]; ICC 0.887 vs. 0.866 for depth, p<0.001). Mean differences between FPCT-A and cast measurements were -1.1 mm for length (p<0.001), -0.7 mm for width (p<0.001) and -0.4 mm for depth (p = 0.023). By MR-A, there were no significant differences for length and width compared to cast (p>0.05). Depth measurements were significantly smaller by MR-A (mean difference -1.1 mm, p<0.001). There was no bias between the different modalities. Conclusions Ex vivo FPCT-A and MR-A both deliver high diagnostic accuracy for the evaluation of osteochondral defects. FPCT-A was slightly more accurate than MR-A, which was most significant when measuring lesion depth.